The influence of communistic idea to modern Chinese literature (Based on the analysis of the Luo Guang bin’s novel «Red Rock») - Aбaилдaевa Г. Н. (Journal of Oriental Studies, 2017)
In the article by a brief overview of the Luo Guang Bin’s nove l “Red Rock” considered the influence of communist idea to the modern Chinese literature. Determine the influence of communist idea to modern Chinese literature allows to recognize a wide range of self-image of Chinese literature of that time.